Pelatihan Jurnalisme Televisi di Era Digitalisasi dan Konvergensi - Rahmadani, Rina (Jurnal Abdimas: Sosial, Bisnis, dan Lingkungan, 2024)
Media convergence has brought almost a major alter in how news coverage is done. News coverage is moving to advanced, intelligently, and interactive media narrating, as well as free, multi-skilled, and technology-powered news generation. One journalist is presently required to report and create news for all diverse designs. Within the computerized and joining time, journalist are required to report their scope to diverse stages, whether to print, tv, or online. Photojournalists, for case, are required to be able to record recordings and type in for TV or online. Moreover, online journalist must be able to record recordings and do live reports on TV. In the interim, TV journalists must be able to require photographs and compose for print and online media. This noteworthy alter within the work of journalist is the premise for the significance of writer training for understudies of SMK Strada 1 in Jakarta. The preparing points to supply an presentation and aptitudes on how to ended up a journalist within the advanced and meeting period. So that SMK understudies as of now know from an early age how journalist work within the current advanced and merging period. In any case, multi-skilled and multi-tasking journalist increment cost-effectiveness, reorganize newsrooms and give a great reason for cutbacks. Media organizations can cut costs due to expanded efficiency and less journalist required.